Human Resource Management Practices to Improve Employee Work (Case Study at Mixue Telang Company) - Diva Ayu Syafitri; Ridwan, Muhammad Farghani; Alfiyan Moh. Zaim; Ismail, Iriani (Formosa Journal of Applied Sciences, 2023)
This research aims to prove that human resource management practices can improve the performance of an employee using a qualitative approach method with descriptive research. This research uses data collection techniques through observation and interviews. Based on this research, it is known that the HRM practices implemented by the company consist of recruitment and selection, appointment and placement of employees, training orientation, workplace placement and development. The population in this study were Mixue employees in Telang, Madura. The sample in this research was 3 respondents. In the process of collecting data in this research, the research used a structured interview method. The data used is primary data that has been obtained through direct interviews. The research results show that HRM practices can improve the performance of employees in Mixue Telang, Madura.